Exploring Student Perceptions of Shadowing Technique as a Self-Directed Pronunciation Practice - Suci Setia Cahya Ningrum; Pasca Kalisa (Universitas Nurul Jadid, 2026)
This study explores the perceptions of English as a Foreign Language students regarding the shadowing technique to conduct self-directed pronunciation practice. Using a descriptive qualitative design, data were obtained through questionnaires and semi-structured interviews administered to 35 Universitas Negeri Semarang EFL students. From the coding process, three emergent themes were identified, namely: (1) perceived suitability of shadowing for self-directed pronunciation practice, (2) perceived improvement in pronunciation skills, and (3) challenges and coping strategies in independent shadowing. The results showed that students view shadowing as a flexible, practical, and autonomous means of learning that enables them to handle their own learning pace with the help of online media. They reported improvements in pronunciation accuracy, recognition of vowels and consonants, and mastery of suprasegmental aspects such as intonation, stress, and rhythm. Challenges also emerged, such as fast native speaker input and limited feedback, which they addressed by adjusting audio speed, recording themselves, and using online dictionaries. Overall, shadowing was perceived not only as a tool for improving pronunciation but also as a means of fostering learner autonomy and metacognitive awareness.